Energy and Exergy Analyses of Forced Draft Fan for Marine Steam Propulsion System during Load Change - Vedran Mrzljak; Paolo Blecich; Nikola Anđelić; Ivan Lorencin (Journal of Marine Science and Engineering, 2019)
A forced draft fan, used for the supply of combustion air into the steam generator of the conventional liquefied natural gas (LNG) carrier was analyzed from the aspect of energy and exergy. The power delivered from the induction motor to the fan was calculated using the manufacturer’s data. The most significant impact on the fan energy power losses is from the air temperature difference between the fan outlet and inlet. The fan energy power losses are inversely proportional to the fan energy efficiency, and the values are between 19.9% and 63.4%, for the entire range of observed steam system loads. The fan exergy destruction depends primarily on the driving power and on the air mass flow rate. At higher loads, an important influence on the fan exergy destruction is from the air pressure at the fan outlet. The exergy efficiency change of the analyzed fan, for the range of observed steam system loads, is directly proportional to the rate of change in the air mass flow, whereas the obtained values of exergy efficiency are between 5.10% and 53.93%. The impact of ambient temperature on the fan exergy destruction and exergy efficiency exhibits is different than in most other steam system components. A change in ambient temperature of 10 °C causes a change in the exergy efficiency of the forced draft fan less than 0.5% in the entire range of observed steam loads.